Quality Attributes: Consumers' Evaluation of Tailored Clothing in Ghana - Alhassan, Haruna Alhassan; Appiah, Ninette Afi; Ankai, Boateng Kojo (Journal of Marketing Studies, 2023)
Purpose: There are challenges in arriving at quality garments that meet the consumers' specifications for Ghanaian fashion designers. To appreciate consumers' conceptualization of quality attributes of tailored clothing produced by small-scale garment manufacturers, the study assessed the quality attributes of tailored clothing produced by small-scale garment manufacturers. Methodology: The descriptive research design was adopted. The study further employed the quantitative data collection and analysis technique. This study's population comprised all clothing product consumers in the Wa Metropolis in the Upper West Region of Ghana. In determining the sample size of consumers, the study resorted to the convenience sampling technique and selected a sample size of 400 consumers. Descriptive and inferential analysis and interpretation (mean and standard deviation) was used. Findings: The study found that consumers are more likely to accept a manufacturer's reputation or brand, the clothing's price, and whether it seems perfectly tailored as indicators of the garment's quality and that they do not evaluate the quality of tailored clothing based on convenience and how difficult it is to come by tailored clothing that fit accurately. Contributions to Theory, Policy and Practice: The study provides insights into consumer behavior in the context of the clothing industry in Ghana and other developing countries and help in explaining how tailoring habits or industry may differ from other more developed countries. Practically, this is useful for manufacturers, retailers, and researchers in the clothing industry who are looking to understand consumer preferences and improve the quality of their products. The findings can be used to inform policies aimed at increasing consumer confidence in the quality of tailored clothing in Ghana which may include measures such as mandatory quality testing or certification programs.